Challenges of democratic constitutionalism in Latin America - Gargarella, Roberto (2025)
This text critically examines the challenges to democratic constitutionalism in Latin America, focusing on the structural tension between the expansion of rights catalogs and the maintenance of a concentrated power structure, particularly within the executive branch.In this regard, the text highlights Latin America’s most significant contributions to global constitutionalism while simultaneously identifying persistent shortcomings in institutional design. These shortcomings have led to a profound gap between normative promises and their actual effectiveness, eroding the legitimacy of the constitutional order. In response, the author proposes rethinking constitutionalism from the perspective of a substantive democracy that is not merely reduced to electoral mechanisms but is understood as a deliberative process between elections.